Service quality in Malaysian Islamic Banks: Empirical Study - Abdul Razak, Dzuljastri; Fodol, Mohamed Zakaria; Jama, Ahmed Abdilahi; Burhan, Ali Ahmad (Research Centre for Islamic Economics (IKAM), 2020)
Service quality is an important and effective tool for banks to achieve customer satisfaction and earn their loyalty, especially under intense competition. Indeed, there is a strong competition between Islamic banks in Malaysia whereby each practitioner is working hard to satisfy their customers’ needs for service excellence. There are few studies that have included Shariah compliance with five other variables namely tangibles, reliability, responsiveness, assurance and empathy known as CARTER model however, majority of these studies have not been conducted for Malaysia. The few studies that were conducted for Malaysia used only descriptive statistics and their sample sizes were small. Hence, this study addresses this gap by conducting the survey in Klang valley region which includes Kuala Lumpur, Gombak and Shah Alam. The method was carried out by conducting a survey of 300 respondents. Data is analyzed using factor analysis and multiple regressions to measure the relationship between the variables. The results indicated that compliance, reliability, and empathy have a positive relationship with customer satisfaction and are significant while assurance, tangibility, and responsiveness are insignificant. Hence, practitioners can emphasize on the three significant factors in improving their service quality. The academicians can benefit by conducting further research into this body of knowledge.